Increased presence of oxidized low‐density lipoprotein in the left ventricular blood of subjects with cardiovascular disease. Issue 6 (31st March 2016) - Aluganti Narasimhulu, Chandrakala; Litvinov, Dmitry; Sengupta, Bhaswati; Jones, Danielle; Sai‐Sudhakar, Chittoor; Firstenberg, Michael; Sun, Benjamin; Parthasarathy, Sampath
Abstract: Oxidized LDL (Ox‐LDL) and oxidative stress have been implicated in both atherosclerosis and congestive heart failure (HF) development. Here, we tested whether Ox‐LDL levels in left ventricular blood (LVB) might differ from those of venous peripheral blood (PB), and whether the level might depend on cardiac function. We also tested whether the LDL molecule is likely to have a longer residence time in the left ventricle of HF subjects with low ejection fraction (EF). The aim of this study was to determine Ox‐LDL levels, paraoxonase 1 (PON1) activity, and cholesterol efflux capacity (CEC) of PB and LVB, and correlate these values with LVEF. Sixty‐one HF patients underwent preoperative transthoracic echocardiographic assessment of ventricular function. LVEFs were determined using Simpson's biplane technique. LVB and PB levels of Ox‐LDL were determined, and PON1 activity and plasma cholesterol efflux capacity were measured. A significant increase in the levels of Ox‐LDL in LVB was noted as compared to levels in PB, even when EF was near normal. However, as ejection fraction decreased, the level of Ox‐LDL in PB approached that of the LVB. PON1 activity and cholesterol efflux studies indicated increased oxidative stress in LVB and a decreased ability to promote cholesterol efflux from lipid‐enriched macrophages. The results suggest that LVB is more oxidatively stressed compared to PB, and therefore LV tissue might be affected differently than peripheral tissues. We recently reported that brain natriuretic peptide (BNP), a marker for HF, is induced by Ox‐LDL, so it is possible localized factors within the LV could profoundly affect markers of HF. Abstract : This study demonstrates that Ox‐LDL levels in left ventricular blood (LVB) is different from those of venous peripheral blood (PB), even when EF is near normal. PON1 activity and cholesterol efflux studies indicate increased oxidative stress in LVB and a decreased ability to promote cholesterol efflux from lipid‐enriched macrophages.